Rhabdoid and Undifferentiated Phenotype in Renal Cell Carcinoma: Analysis of 32 Cases Indicating a Distinctive Common Pathway of Dedifferentiation Frequently Associated With SWI/SNF Complex Deficiency - Agaimy, Abbas; Cheng, Liang; Egevad, Lars; Feyerabend, Bernd; Hes, Ondrej; Keck, Bastian; Pizzolitto, Stefano; Sioletic, Stefano; Wullich, Bernd; Hartmann, Arndt (American Journal of Surgical Pathology, 2017)
Undifferentiated (anaplastic) and rhabdoid cell features are increasingly recognized as adverse prognostic findings in renal cell carcinoma (RCC), but their molecular pathogenesis has not been studied sufficiently. Recent studies identified alterations in the Switch Sucrose nonfermentable (SWI/SNF) chromatin remodeling complex as molecular mechanisms underlying dedifferentiation and rhabdoid features in carcinomas of different organs. We herein have analyzed 32 undifferentiated RCCs having in common an undifferentiated (anaplastic) phenotype, prominent rhabdoid features, or both, irrespective of the presence or absence of conventional RCC component. Cases were stained with 6 SWI/SNF pathway members (SMARCB1, SMARCA2, SMARCA4, ARID1A, SMARCC1, and SMARCC2) in addition to conventional RCC markers. Patients were 20 males and 12 females aged 32 to 85 years (mean, 59). A total of 22/27 patients with known stage presented with >=pT3. A differentiated component varying from microscopic to major component was detected in 20/32 cases (16 clear cell and 2 cases each chromophobe and papillary RCC). The undifferentiated component varied from rhabdoid dyscohesive cells to large epithelioid to small monotonous anaplastic cells. Variable loss of at least 1 SWI/SNF complex subunit was noted in the undifferentiated/rhabdoid component of 21/32 cases (65%) compared with intact or reduced expression in the differentiated component. A total of 15/17 patients (88%) with follow-up died of metastatic disease (mostly within 1 y). Only 2 patients were disease free at last follow-up (1 and 6 y). No difference in survival, age distribution, or sex was observed between the SWI/SNF-deficient and the SWI/SNF-intact group. This is the first study exploring the role of SWI/SNF deficiency as a potential mechanism underlying undifferentiated and rhabdoid phenotype in RCC. Our results highlight the association between the aggressive rhabdoid phenotype and the SWI/SNF complex deficiency, consistent with studies on similar neoplasms in other organs. Thorough sampling of such tumors that are usually huge and locally advanced is necessary for recognizing the clone of origin and hence for proper subtyping and also for differentiating them from undifferentiated urothelial carcinoma.
EVALuna2:6840